SIFAT MUDAH PUTUS ASA SIFAT MUDAH PUTUS ASA PADA MAHASISWA SALAH TUJUAN: SIFAT MUDAH PUTUS ASA PADA MAHASISWA SALAH TUJUAN - Adriansyah Permana; Alvin Raviksyah Putra; Muhammad Bagus Prasetyo (Jurnal Psikologi Islam, 2021)
In modern times like this education is very important, many students after graduating from SMA / SMK choose to enter university. It can be said that Higher Education is a place for students who have different talents, interests and motivations. Usually students have several reasons for entering college, for example, such as parents, following trends, environmental influences through joining in with friends and many other reasons. However, it can also backfire for students who wish to enter university, because they only choose a major without requiring their application. Sometimes there are students who want to enter a department just because of the problem of the job they want but are not in accordance with the major. Finally, there was a feeling of depression and despair after choosing the wrong direction. Keywords: student, wrong goal, despair.